Aflatoxin-albumin adduct formation after single and multiple doses of aflatoxin B(1) in rats treated with Thai medicinal plants - Vinitketkumnuen U. (2014)
The objective was to conduct an assessment of the ability of two Thai medicinal plants, Cymbopogon citratus Stapf and Murdannia loriformis, to modulate levels of serum aflatoxin-albumin (AF-albumin) adducts following aflatoxin B(1) (AFB(1)) exposure in rats. The influence of the plant extracts on AF-albumin adduct formation after a single exposure to 250 microg/kg body weight (bw) AFB(1) was measured over a 48-h period. Rats received M. loriformis extract (3 g/kg bw) or C. citratus Stapf extract (5 g/kg bw) daily for the week prior to the AFB(1) administration. In control rats, maximum adduct levels were observed 12 h post-AFB(1) treatment but in the animals receiving Murdannia extract, maximum levels occurred earlier, at 4 h post-treatment. No such effect was observed with the Cymbopogon extract. Daily treatment of rats with AFB(1) at 250 microg/kg bw for 3 weeks caused serum AF-albumin adduct levels to accumulate over a 10-14 day period and reach plateau levels 4.4-fold higher than observed after a single dose. Treatment with Murdannia extract for 1 week before and then throughout the AFB(1) exposure period resulted in a slight decrease in the AF-albumin adduct levels in the first week of the intervention. After that time, however, the reduction in adduct levels in the Murdannia extract group did not differ significantly from controls. No significant alteration in the biomarker levels was seen with the Cymbopogon extract treatments compared to control rats.